Kajian Penerapan Interpretasi Standar Akuntansi Keuangan (ISAK) 35 pada Pondok Pesantren - Listiyowati (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2021)
Financial accountability in Islamic boarding schools is still experiencing obstacles in addition to internal factors in the form of existing human resources, there are also external factors in the form of implementation of financial accounting standards that have not been used optimally. Meanwhile, Islamic boarding schools in Indonesia number in the tens of thousands and most Islamic boarding schools have business units in building an independent economy. The financial standard used is SAK Syariah because Islamic boarding schools are sharia entities. Meanwhile, to make financial reports where Islamic boarding schools are legal entities, they use the ISAK 35 standard regarding the presentation of financial statements of non-profit entities as of January 1, 2020, which replaces the previous PSAK, namely PSAK 45. ISAK 35 contains comprehensive income which includes net assets with restrictions and limitations. without restrictions.